2001
DOI: 10.1177/875697280103200206
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Risk Management Matrix for Effective Project Planning—An Empirical Study

Abstract: This paper presents a risk management matrix for effective planning of industrial projects. A schematic view of the project environment has been suggested to systematically identify the effects of various project environments, and thereby take a holistic view of risks arising out of immediate and external environments. Various subfactors within each risk element are presented. A process to quantify the immediate and external risks for industrial projects using a weighted probability method is proposed. To deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Another feature of the economic infrastructure projects is that they tend to have poor performance (Datta & Mukherjee, 2001;Chan & Chan, 2004;Shen et al, 2006;Flyvbjerg, 2007Flyvbjerg, , 2008Eriksson & Westerberg, 2011). In the study conducted by Flyvbjerg et al (2002) when examining transport projects found that 90% had the cost overruns.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Another feature of the economic infrastructure projects is that they tend to have poor performance (Datta & Mukherjee, 2001;Chan & Chan, 2004;Shen et al, 2006;Flyvbjerg, 2007Flyvbjerg, , 2008Eriksson & Westerberg, 2011). In the study conducted by Flyvbjerg et al (2002) when examining transport projects found that 90% had the cost overruns.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The risk assessment process is one of the most applied by managers (Lyons & Skitmore, 2004), but the lack of ability for the execution of this task limits their efficiency (Globerson & Zwikael, 2002;Raz et al, 2002). Thus, it should be noted that the performance impact of the projects varies with the level of presence of risk factors (Datta & Mukherjee, 2001;Ng & Loosemore, 2007) and with the risk factor type involved in the project (Ghosh & Jintanapakanont, 2004;Thamhain, 2013).…”
Section: /43mentioning
confidence: 99%
“…Numerous authors (Datta and Mukherjee, 2001;Ward, 1999) stress the importance of understanding the project environment to initiate any assessment of risk. In NEPA processes, that environment is influenced by multiple factors, some of which are determined at the outset of the process as the project is initially defined.…”
Section: Risk Sourcesmentioning
confidence: 99%
“…Relationship risk includes risk that can emerge from both internal and external relationships (Datta and Mukherjee, 2001;Hillson, 2003;Tesch et al, 2007). External relationships have been well-studied in natural resource management, with multiple studies focusing on public involvement, conflict, collaboration, and their outcomes (Innes and Booher, 2004;Leach, 2006;Lewicki et al, 2002;McCool and Guthrie, 2001;Predmore et al, 2011a;Wondolleck and Yaffee, 2000).…”
Section: Risk Sourcesmentioning
confidence: 99%
“…Price (1998) defi nes risk as the probability times multiple consequences using a probabilistic fault tree approach. Datta and Mukerjee (2001) developed a nine-segment matrix for immediate project risk analysis based on weighted probability. Pyra and Trask (2002) describe a quantitative priority ranking based on a table of probability and impact.…”
Section: Risk Terminologymentioning
confidence: 99%